2008
DOI: 10.1016/j.oraloncology.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel single nucleotide polymorphism in XRCC4 gene is associated with oral cancer susceptibility in Taiwanese patients

Abstract: The DNA double strand break repair gene XRCC4, an important caretaker of genome stability, is suggested to play a role in the development of human carcinogenesis. However, no evidence has been provided showing that XRCC4 was associated with oral oncology. In this hospital-based case-control study, the association of XRCC4 G-1394T (rs6869366), intron 3 (rs28360071), intron 7 (rs28360317), and intron 7 (rs1805377) polymorphisms with oral cancer risk in a Taiwanese population was first investigated. In total, 318… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 18 publications
1
54
1
Order By: Relevance
“…There are already plenty of approaches which aim at the genetic risk factors of glioma and meningiomas, and the polymorphisms of DNA repair system have been thought to be related with various cancers (Chiu et al, 2008;Kiuru et al, 2008;Mandal et al, 2011;Zhou et al, 2011;Mittal et al, 2012). All these findings strengthen the linkage of DNA repair systems, genome instability and carcinogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…There are already plenty of approaches which aim at the genetic risk factors of glioma and meningiomas, and the polymorphisms of DNA repair system have been thought to be related with various cancers (Chiu et al, 2008;Kiuru et al, 2008;Mandal et al, 2011;Zhou et al, 2011;Mittal et al, 2012). All these findings strengthen the linkage of DNA repair systems, genome instability and carcinogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Genomic DNA was prepared from peripheral blood leukocytes using a QIAamp Blood Mini Kit (Blossom, Taipei, Taiwan) and further processed as previously described (4)(5)(6)(7)(8)(9)17,18). The following primers were used: for XRCC4 C-1622T rs7727691, 5'-AAGATACTGAGACACTA ATC-3' and 5'-CACAACATAACTAAGGATGA-3'; for XRCC4 G-1394T rs6869366, 5'-GATGCGAACTCAAAGA TACTGA-3' and 5'-TGTAAAGCCAGTACTCAAACTT-3'; for XRCC4 C-571T rs2075686, 5'-GGCTACTGACTAAAC AGATG-3' and 5'-TAACACGTTGGCTACGTAGA-3'; and for XRCC4 intron3 DIP rs28360071, 5'-TCCTGTTACCATT TCAGTGTTAT-3' and 5'-CACCTGTGTTCAATTCCAG CTT-3'.…”
Section: Methodsmentioning
confidence: 99%
“…These genetic polymorphisms, especially those located on the DNA repair system genes, can be considered potential risk factors for the disease. The DNA repair system is one of the most delicate and important defenses against cancer, and deficient function of this system has been reported to lead to many lethal diseases, including various cancers (4)(5)(6)(7)(8)(9). The genes of the DNA repair system are therefore reasonable candidates for the identification of novel biomarkers in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms in DNA repair genes such as EXO1 are thought to modulate DNA repair capacity and consequently are suggested to be associated with colorectal cancer [22]. Singlenucleotide polymorphism (SNP) is a DNA sequence variation and has a great potential application to determine association with susceptibility to several cancers such as oral, breast, prostate, gastric and colorectal cancer [23][24][25][26][27][28][29][30][31]. These indicate that substitution in these SNPs may effect on genes' functions or expression levels.…”
Section: Introductionmentioning
confidence: 99%
“…So, risky genotypes have an effect on cancer susceptibility [20]. Wu et al [32] reported 12 missense single nucleotide polymorphisms in the EXO1 gene including K589E in exon11 [21][22][23][24][25][26][27][28][29][30][31][32]. An exonic SNP doesn't necessarily cause a dysfunctional protein.…”
Section: Introductionmentioning
confidence: 99%